Nitric and nitrous oxide reductases are active under aerobic conditions in cells of Thiosphaera pantotropha. - Bell, L C (1991)
Use of Clark-type electrodes has shown that, in cells of Thiosphaera pantotropha, the nitrous oxide reductase is active in the presence of O2, and that the two gases involved (N2O, O2) are reduced simultaneously, but with mutual inhibition. Reduction of nitrate, or nitrite, to N2O under aerobic conditions involves NO as an intermediate, as judged by trapping experiments with the ferric form of extracellular horse heart cytochrome c and the demonstration that the cells possess a nitric oxide reductase activity. The overall conversion of nitrate to N2, the process of denitrification, under aerobic conditions, is thus not prevented by reaction of NO with O2 and depends upon a nitrous oxide reductase system which differs from that in other organisms by being neither directly inhibited nor inactivated by O2.